Effect of IBA (Indole Butyric Acid) Concentration on the Growth of Avocado Plant Cuttings (Persea americana Mill) - Maulida Safira; Agus Sulistyono; Ida Retno Moeljani (The University of Lampung, 2025)
The demand for avocados in Indonesia continues to rise, while the availability of high-quality seedlings remains limited. Propagation through stem cuttings with the application of IBA (Indole Butyric Acid) is expected to improve propagation success. This study aims to determine the effect of IBA concentration on the growth of avocado stem cuttings. The research was conducted in Bojonegoro, East Java, using a Completely Randomized Design (CRD) with one factor, namely five concentrations of IBA: 0, 75, 100, 125, and 150 ppm. Observed parameters included shoot length, number of shoots, number of leaves, and number of primary roots. The results showed that IBA concentration had a significant effect on all observed parameters, while cutting length had no significant effect. A concentration of 100 ppm produced optimal growth of 1.92 cm, 2.50 shoots, and 4.33 leaves. The treatment without IBA resulted in the lowest values. The application of IBA at concentrations of 75–100 ppm effectively enhanced the growth of avocado stem cuttings, particularly in shoot and leaf development.